PARENT’S PERSPECTIVES OF SCHOOL-AGE ANXIETY RESPONSES GET IV INSTALLATION - Indira Mastura Pulungan; Nur Asnah Sitohang (OISAA, 2021)
The IV installation procedure is an invasive procedure that children fear because of the use of needles. The IV procedure can cause anxiety for the child. Children's anxiety is indicated by worry, anxiety, and physical complaints. This study aims to determine how child's anxiety responds to get IV installation based on the parents’ perspectives. This research method is a cross-sectional descriptive study. The sampling technique in this study was total sampling with 69 respondents. Respondents in this study were parents who had school-age children with IV installation experience for a maximum of the last 2 years. The questionnaire was given via Google Form because of the research period on coronavirus pandemic. The results showed that the majority of school-age children showed a response with fear in 71%, closed their eyes in 67%, and showed a tense and pale facial expression when the IV installation was inserted in 67%. School-age children require the presence of parents in dealing with hospital procedures, especially IV installation. School-age children also need an explanation regarding the procedures given. The children will feel calmer when they know how the procedure is given.